STRATEGI VISUAL PADA INFOGRAFIS AQUA RAMADHAN 242 (HARMONISASI PARADOKS VISUAL PADA PENGGUNAAN 2 GAYA DESAIN) - Rifki Aswan (Narada : Jurnal Desain dan Seni, 2020)
Infographics can reduce the use of words that are not needed and can package messages to become more interesting. Research on Aqua 242 infographics of Ramadhan uses a qualitative method with a case study approach to identify the appropriateness of health infographic principles and visual strategies in the paradoxical visual style applied by the Ramadhan AQUA 242 campaign infographics. To find out the visual strategy adopted by the Y&R design team in overcoming the problem. Fill in the summary.